Flow Dependence of Carbon Dioxide Corrosion Using Short Electrodes by Jet Impingement - John, Doug; Kinsella, Brian; Bailey, Stuart; De Marco, Roland (NACE International, 2009)
The jet impingement technique is a valuable methodology for the evaluation of carbon dioxide corrosion and inhibition under high flow velocities. This technique commonly employs short electrodes that remain within a region of the developing diffusion boundary layer induced by the reactively corroding surface. The employment of such electrodes has been associated with the poor correlation of corrosion rates determined from field and laboratory measurements by various apparatus. This paper presents an investigation into the flow relationship of the carbon dioxide corrosion mechanism in non-scaling synthetic brine solutions at 30 C with a carbon dioxide partial pressure of 1.88 bar. The effect of the developing diffusion boundary layer on the corrosion rate and its dependence on the flow velocity is investigated by jet impingement using dissimilar electrode lengths in the flow direction.It is shown that the measured corrosion rate is dependent on the state of development of the diffusion boundary layer with a relationship that is contrary to the average rate of mass transfer. A more developed diffusion boundary layer exhibits a greater rate of carbon dioxide corrosion at a lower average mass transfer than in a developing diffusion boundary layer with a higher average mass transfer. This phenomenon illustrates an antagonistic effect of the diffusion boundary layer on the mechanism of carbon dioxide corrosion that is likely to strongly influence the correlation of corrosion rates obtained using various laboratory apparatus and field applications.